Model Partisipasi Masyarakat Dalam Program Kampung Siaga Aktif di Kampung Salor Indah Distrik Kurik Kabupaten Merauke - Irawan, Andri (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
The high rate of maternal and infant mortality shows that the quality of health services is still low, and an active alert village has been made to create a healthy lifestyle for the community. Active Alert Campaign Study in Salor Indah Village in Merauke Regency and the factors that influence it. This research uses descriptive type using qualitative. Data obtained through key informants determined purposively. The results of the study show that; (1) Salor Indah Village has fulfilled the criteria specified in the active standby village program. (2) Community participation based on the CLEAR model which contains sources of information and knowledge obtained by the community, consisting of posters and active standby village service instructions, and the community to get convenience in using active standby village facilities. Every idea taken by the community is taken as input in the leadership decision making. These ideas and thoughts were conveyed during the Village Community Consultation. (3) The inhibiting factor in the implementation of the active Alert Village program is the quality of human resources owned by Kampung Siaga not yet competent in the health sector, the community is still weak to receive information about low educational background, and also the difficulty of paying attention to the community open a healthy life.